Influence of Time and Direction Information on Video Head Impulse Gains. - Yılmaz, Oğuz; Öz, Ersoy; Kurt, Serkan; Aşkın, Öyküm Esra; Taşdemir, Elifnur; Mutlu, Berna Özge; Keleş, Ahmet; Cevizci, Raşit (My University, 2017)
The objective of this study was to establish which factor leads to a higher vestibulo-ocular reflex (VOR) gain: the timing of the movement or the direction of the movement. For this purpose, healthy volunteers were examined under three conditions: (1) when they were informed about the timing of the head movement; (2) when they were informed about the direction of the head movement; and (3) when they knew both the timing and the direction of the head movement.

This study included data from 19 participants between the ages of 20 and 23 years with no neurological or vestibular ailments. The gains of the video head impulse test (vHIT) were measured under four different conditions and the final control tests. Five subgroups were defined, and the differences in the subgroups were assessed with using several statistical procedures.

We found that there were significant differences between all subgroups gains on the right and left head rotations. Nevertheless, nonsignificant differences were found by performing independent samples t-tests and Mann-Whitney U tests between left and right head rotations for the pairwise comparisons of subgroups. Also, analysis of variance (ANOVA) results indicated that vHIT gains for the right and left , respectively). Thus, knowing the timing or direction or both does not affect vHIT gains.

The results of these experiments revealed that there is no association whatsoever between VOR gain and awareness of the timing or direction of the movement or both.